Ultrasonographic Evaluation of Canine Supraspinatus Calcifying Tendinosis - Mistieri, Maria Ligia A.; Wigger, Antje; Canola, Julio C. [UNESP]; Filho, Joao G. P. [UNESP]; Kramer, Martin (Amer Animal Hospital Assoc, 2012)
Supraspinatus calcifying tendinosis is an uncommon finding in dogs. Although its radiographic appearance has been described previously, radiographs alone do not provide detailed information about the tendon parenchyma. Tendon ultrasonography has been widely applied for the diagnosis of human tendinosis, but it remains underused in dogs. This article reviews the ultrasonographic technique and variable appearance of canine supraspinatus calcifying tendinosis observed in 33 tendons. The ultrasonographic findings are described. The most common ultrasonographic finding was a hyperechoic area accompanied by distal acoustic shadowing. No relationship with bicipital tenosynovitis was found. A color Doppler examination was possible in only five of the tendons, revealing no blood flow in those tendons. There was evidence that the presence of a hypoechoic area surrounding the calcification was related to clinical signs of pain, suggesting an active inflammatory process. Ultrasonography was an excellent technique to evaluate lesions of the supraspinatus tendon and it revealed details not apparent on radiographs. (J Am Anim Hosp Assoc 2012; 48:405-410. DOI 10.5326/JAAHA-MS-5818)